Magnesium Nanoparticles With Pd Decoration for Hydrogen Storage - Liu, Yana; Zhu, Jinglian; Liu, Zhibing; Zhu, Yunfeng; Zhang, Jiguang; Li, Liquan (Frontiers in Chemistry, 2020)
In this work, Magnesium nanoparticles with Pd decoration, ranging from 40 to 70 nm, were successfully coprecipitated from tetrahydrofuran (THF) solution, assigned as the Mg–Pd nanocomposite. The Mg–Pd nanocomposite exhibits superior hydrogen storage properties. For the hydrogenated Mg–Pd nanocomposite at 150°C, the onset dehydrogenation temperature is significantly reduced to 216.8°C, with a lower apparent activation energy for dehydrogenation of 93.8 kJ/mol H2. High-content γ-MgH2 formed during the hydrogenation process, along with PH0.706, contributes to the enhancing of desorption kinetics. The Mg–Pd nanocomposite can take up 3.0 wt% hydrogen in 2 h at a temperature as low as 50°C. During lower hydrogenation temperatures, Pd can dissociate hydrogen and create a hydrogen diffusion pathway for the Mg nanoparticles, leading to the decrease of the hydrogenation apparent activation energy (44.3 kJ/mol H2). In addition, the Mg–Pd alloy formed during the hydrogenation/dehydrogenation process can play an active role in the reversible metal hydride transformation, destabilizing the MgH2.